Corrigendum to “Catch and release of deep energy sources across orogenic cycles” [Geochim. Cosmochim. Acta 426 (2026) 93–109] - Orlando Sébastien Olivieri; Francesco Ressico; Thomas Gusmeo; Isabelle Daniel; Antoine Boutier; Veronica Peverelli; Zeudia Pastore; Mark Van Baalen; Jens Fiebig; Alberto Vitale Brovarone (Geochimica et Cosmochimica Acta, 2026)

Catch and release of deep energy sources across orogenic cycles - Orlando Sébastien Olivieri; Francesco Ressico; Thomas Gusmeo; Isabelle Daniel; Antoine Boutier; Veronica Peverelli; Zeudia Pastore; Mark Van Baalen; Jens Fiebig; Alberto Vitale Brovarone (Geochimica et Cosmochimica Acta, 2026)

Fate of persistent and mobile substances in drinking water treatment: A systematic comparison of treatment options - Pia Schumann; Luisa Rabe; Malte Zamzow; Isabelle Neuwald; Thomas P. Knepper; Matthias Muschket; Daniel Zahn; Pascal Hasselder; Thorsten Reemtsma; Martin Jekel; Aki Sebastian Ruhl (Journal of Hazardous Materials, 2026)

Nature vs. nurture? Light availability drives phenotypic plasticity within a reef coral species - Hugo Ducret; Christopher R. Suchocki; Claire J. Lewis; Heidi M. Dierssen; Eric J. Hochberg; Daniel W. H. Schar; Marc Kochzius; Isabelle F. George; Robert J. Toonen; Jean‐François Flot (Limnology and Oceanography, 2026)
Scleractinian corals exhibit wide intra‐specific phenotypic variations. However, the extent to which these variations are explained by genotypic variation or phenotypic plasticity remains unclear. To elucidate this question, we devised a replicated experiment in which nine Montipora capitata coral colonies were cut into six pieces each, three of which were placed in shaded conditions (with a 73% reduction in light intensity) whereas the other three were kept in natural conditions as a control. After 1 year, we detected statistically significant morphological differences between corals of the same genotypes grown in different light environments, but no significant change in symbiont community structure. Colonies kept in control conditions exhibited a high surface complexity and converged toward more digitate or corymbose morphs compared to shaded corals, which exhibited planar‐like surfaces and converged toward laminar and foliose forms. Our data demonstrate the high level of light‐driven phenotypic plasticity of M. capitata and suggest a trade‐off between the amount of biomass per space area and the amount of absorption of incident light.

Occurrence, patterns and previously overlooked sources of three veterinary ectoparasiticides in rural and urban Welsh rivers - Molly Hadley; Laura Rodwell; Matt Stewart; Daniel Crowther; Jasper Linley-Adams; Sian Craig; Suzanne Thomas; Anthony Gravell; Isabelle Durance; Ian P. Vaughan; S.J. Ormerod (Environmental Pollution, 2026)

Intracellular Amorphous Calcium Carbonate Biomineralization in Methanotrophic Gammaproteobacteria Was Acquired by Horizontal Gene Transfer From Cyanobacteria - Karim Benzerara; Maxime Millet; Fériel Skouri‐Panet; Geoffroy Gaschignard; Neha Mehta; Malo Bezard; Géraldine Caumes; Daniel M. Chevrier; Manuela Dezi; Arnaud Duverger; Jean‐Michel Guigner; Ana Gutiérrez‐Preciado; et al. (Environmental Microbiology, 2026)
Some bacteria genetically control the biomineralisation of intracellular amorphous calcium carbonates (iACC) with potential implications for microbial physiology, evolution, bioremediation and biogeochemical cycling. Until now, this capacity has been documented in Cyanobacteria , the giant gammaproteobacterium Achromatium and a few magnetotactic Pseudomonadota and Nitrospirota . Here, we report the discovery of iACC biomineralisation in members of the Methylococcaceae , a family of aerobic methanotrophic Gammaproteobacteria . A homologue of the ccyA gene, a diagnostic marker for iACC formation in Cyanobacteria , was identified in several Methylococcaceae genomes, based on the conserved C‐terminal (GlyZip)3 domain of the encoded calcyanin protein. Moreover, two cultivated strains, Methylococcus geothermalis and Methylococcus mesophilus , whose genomes contained the ccyA gene, were consistently shown to form iACC. The ccyA genes of Methylococcaceae and Microcystis share higher sequence similarity than with other Cyanobacteria , suggesting horizontal gene transfer (HGT) from an ancestral Microcystis ‐like cyanobacterium to Methylococcaceae . This finding extends the known taxonomic distribution of ccyA and suggests that the capability to biomineralize iACC was acquired by HGT. The discovery of iACC in methane‐oxidising Methylococcaceae highlights a previously unrecognised coupling between calcium carbonate biomineralisation and methane cycling in aquatic environments, suggesting an overlooked role of iACC formation in microbial carbon storage and local geochemical regulation.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Corrigendum to “Identification of caseinophosphopeptides generated through in vitro gastro-intestinal digestion of Beaufort cheese” [Int. Dairy J. 129–134, 0958–6946] - Isabelle Adt; Coralie Dupas; Rachel Boutrou; Samia Dhahri; Nadia Oulahal; Claude Noel; Daniel Mollé; Thierry Jouvet; Pascal Degraeve (International Dairy Journal, 2026)

Diagnosis of Enzootic Bovine Hematuria: Comparative performance of endoscopy and ultrasound in naturally occurring cases - Marina Galindo Chenard; Jade de Menezes Paes; Josielle de Almeida Pereira; Luiz Filipe Cabral de Souza Ramos; Yohany Arnold Alfonso Pérez; Kicia Russano; Vivian de Assunção Nogueira Carvalho; Guilherme Nunes de Souza; Isabelle Magalhães da Cunha; Nayro Xavier Alencar; Daniel Augusto Barroso Lessa; Michel Abdalla Helayel (The Veterinary Journal, 2025)

Essential oil emulsions as a strategy to inhibit Aspergillus flavus and aflatoxin production in maize - Naara Aparecida Almeida; Daniel Lucino Silva dos Santos; Raquel Costa Chevalier; Isabelle Dias Vieira; Aildson Pereira Duarte; Rosiane Lopes Cunha; Liliana de Oliveira Rocha (Food Bioscience, 2025)

Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark; Valentin Thomas; Richard S. Taylor; Mathieu Charles; Audrey Laurent; Isabelle Schwartz-Cornil; Bertrand Collet; Delphine Lallias; Daniel J. Macqueen; Samuel A.M. Martin; Pierre Boudinot (Fish & Shellfish Immunology, 2025)

A systematic review and meta-analysis of the effectiveness of work-focused interventions for employees with symptoms of depression, anxiety, and psychological distress - Samineh Sanatkar; Rosie Lipscomb; Katherine Petrie; Daniel Collins; Andrew Arena; Mei Xu; Isabelle Counson; Vita Ligaya Dalgaard; Arnstein Mykletun; Anthony D. LaMontagne; Samuel B. Harvey; Mark Deady (International Archives of Occupational and Environmental Health, 2025)

Air–Water Cross-Contamination by Metalliferous Atmospheric Particulates: Bioaccumulation and Hematological Impairments in the Estuarine Fish Centropomus parallelus - Anieli Cristina Maraschi; Isabelle Cesar Moro; Viviane Gomes dos Santos; Iara Costa Souza; Magdalena Victoria Monferran; Daniel Alberto Wunderlin; Fabiano Bendhack; Marisa Narciso Fernandes; Diana Amaral Monteiro (Bulletin of Environmental Contamination and Toxicology, 2025)

Development of ingestive and social behavior of buffalo calves in a cow-calf contact grazing system - Arthur Fernandes Bettencourt; Francisco Freire Duarte; Isabelle Damé Veber Angelo; Daniel Mota-Rojas; Adriana Domínguez-Oliva; Vivian Fischer (Applied Animal Behaviour Science, 2025)

Redfield revisited: Insights into freshwater seston carbon : nitrogen : phosphorus stoichiometry - Isabelle M. Andersen; Jason M. Taylor; Daniel Graeber; Patrick T. Kelly; Alexa K. Hoke; Caleb J. Robbins; J. Thad Scott (Limnology and Oceanography, 2025)
Seston carbon (C), nitrogen (N), and phosphorus (P) stoichiometry plays a fundamental role in aquatic ecosystems, influencing nutrient cycling, primary and secondary production, and trophic interactions. In freshwater systems such as lakes, P limitation is more common, whereas in marine environments, N more frequently limits primary production, reflecting different nutrient limitation patterns across aquatic ecosystems. The Redfield ratio (C 106 : N 16 : P 1 molar), developed from marine seston, has long been considered a benchmark for nutrient composition and a predictor of nutrient limitation across aquatic ecosystems. A later global freshwater and marine seston survey proposed the Sterner ratio (C 166 : N 20 : P 1 molar) as a broader global seston average. We present the results of a fully replicated, multi‐annual freshwater mesocosm experiment testing the effect of variable resource N : P stoichiometry on seston stoichiometry. We found that the seston C : N : P ratio aligned with the Redfield ratio under N‐limited conditions, while P‐limited conditions aligned with the Sterner global survey of freshwater ecosystems. Ternary plots offered visual insight into stoichiometric shifts, showing a trend toward P depletion relative to C and N as N : P supply increases. The average seston C : N : P ratio observed from our experimental data was C 141 : N 22 : P 1 (molar) and variation in seston C : N : P was small compared to the resource ratio gradient. Our mesocosm experiment showed that the Redfield ratio provides a useful description of seston stoichiometry in N‐limited freshwater ecosystems. These findings advance the understanding of bottom‐up controls on seston C : N : P stoichiometry and highlight the need to refine ecological theories regarding the application of the Redfield ratio in freshwater ecosystems.

Data processing and acquisition geometry impact the estimation of plant trait-based functional richness from airborne imaging spectroscopy - Marius Vögtli; Isabelle S. Helfenstein; Daniel Schläpfer; Meredith C. Schuman; Mathias Kneubühler; Alexander Damm (Remote Sensing of Environment, 2025)

Microsynthesis, mass spectrometry data and acetylcholinesterase inhibition studies of carbamates related to the OPCW 1.A.16 Scheduled Chemicals - Diego G.R. Voris; Munique C. Jesus-Silva; Taynara Carvalho-Silva; Cíntia N. Ferreira; Monique Cardozo; Valdir F.da Veiga Junior; Alessandro B.C. Simas; Bruno G.M. Rodrigues; Isabelle K.da C. Nunes; Leandro B. Bernardo; Daniel A.S. Kitagawa; Antonio L.S. Lima; et al. (Chemico-Biological Interactions, 2025)

Diachronic reconstruction of palaeoclimates and diet through stable isotopes (δ13C and δ18O) and 2D geometric morphometrics from cave bear (Ursus spelaeus) dentition - Daniel Charters; Hubert B. Vonhof; Richard P. Brown; Dominique Bonjean; Isabelle De Groote; Carolin Pellio; Grégory Abrams; Carlo Meloro (Quaternary International, 2025)

Ingestive behavior of dairy buffaloes in a cow-calf contact grazing system during the post-calving - Arthur Fernandes Bettencourt; Francisco Freire Duarte; Isabelle Damé Veber Angelo; Júlia Fernandes Aires; Bruna Martins de Menezes; Anderson Michel Soares Bolzan; Daniel Mota-Rojas; Vivian Fischer (Applied Animal Behaviour Science, 2025)

The complementarity hypothesis reversed: Root trait similarity in species mixtures promotes soil organic carbon in agroecosystems - Shuang Yin; Xinli Chen; Gabin Piton; César Terrer; Zhenghu Zhou; Gerlinde B. De Deyn; Isabelle Bertrand; Daniel Rasse; Ji Chen; Jose Antonio Navarro-Cano; Diego Abalos (Soil Biology and Biochemistry, 2025)

Abiotic carbonaceous matter as a hidden deep carbon reservoir in the serpentinized forearc mantle wedge - Renbiao Tao; Isabelle Daniel; Muriel Andreani; Bénédicte Ménez; Gilles Montagnac; Hervé Cardon; Clémentine Fellah; Yuhang Lu; Zengli Guo (Geochimica et Cosmochimica Acta, 2025)

Innovatives Bemessungsverfahren für Stauanlagen unter Anwendung von Johnson-Verteilungen - Hubert Lohr; Isabelle Huber; Sandra Richter; Gerd Demny; Daniel Bittner (WASSERWIRTSCHAFT, 2025)

Fate of persistent and mobile chemicals in the water cycle: From municipal wastewater discharges to river bank filtrate - Matthias Muschket; Isabelle J. Neuwald; Daniel Zahn; Alina H. Seelig; Jochen Kuckelkorn; Thomas P. Knepper; Thorsten Reemtsma (Water Research, 2024)

Impacts of forest canopy heterogeneity on plot-scale hydrometeorological variables - Insights from an experiment in the humid boreal forest with the Canadian Land Surface Scheme - Philippe Lagueux; Jean-Daniel Sylvain; Guillaume Drolet; Pierre-Erik Isabelle; Gonzalo Leonardini; Daniel F. Nadeau; François Anctil (Agricultural and Forest Meteorology, 2024)

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

WITHDRAWN: Abiotic carbonaceous matter as a hidden deep carbon reservoir in the serpentinized forearc mantle wedge - Renbiao Tao; Isabelle Daniel; Muriel Andreani; Bénédicte Ménez; Gilles Montagnac; Hervé Cardon; Yuhang Lu; Zengli Guo (Geochimica et Cosmochimica Acta, 2024)

Clear-cutting of temperate forests in late successional stages triggers successional setbacks extending compositional recovery by an additional century - Martin Barrette; Daniel Dumais; Isabelle Auger; Yan Boucher (Forest Ecology and Management, 2024)

No association between markers of systemic inflammation and endothelial dysfunction with Alzheimer’s disease progression: a longitudinal study - Arne van Setten; Jeroen F. Uleman; René J. F. Melis; Brian Lawlor; Niels P. Riksen; Jurgen A. H. R. Claassen; Rianne A. A. de Heus; Ricardo Segurado; Sean Kennelly; Marcel G. M. Olde Rikkert; Robert Howard; Florence Pasquier; et al. (GeroScience, 2024)
Introduction Systemic inflammation and endothelial dysfunction are potentially modifiable factors implicated in Alzheimer’s disease (AD), which offer potential therapeutic targets to slow disease progression. Methods We investigated the relationship between baseline circulating levels of inflammatory (TNF-α, IL-1ß) and endothelial cell markers (VCAM-1, ICAM-1, E-selectin) and 18-month cognitive decline (ADAS-cog12) in 266 mild-to-moderate AD patients from the NILVAD study. We employed individual growth models to examine associations, potential mediation, and interaction effects while adjusting for confounders. Results The average increase in ADAS-cog12 scores over all patients was 8.1 points in 18 months. No significant association was found between the markers and the rate of cognitive decline. Mediation analysis revealed no mediating role for endothelial cell markers, and interaction effects were not observed. Discussion Our results do not support the role of systemic inflammation or endothelial dysfunction in progression in persons with AD.

Intra-oceanic emplacement of the Comoros Archipelago through inherited fracture zones - Charles Masquelet; Louise Watremez; Sylvie Leroy; Daniel Sauter; Matthias Delescluse; Nicolas Chamot-Rooke; Jean Claude Ringenbach; Isabelle Thinon; Anne Lemoine; Dieter Franke (Tectonophysics, 2024)

Predicting river phytoplankton blooms and community succession using ecological niche modeling - Michael J. Bowes; Michael G. Hutchins; David J. E. Nicholls; Linda K. Armstrong; Peter M. Scarlett; Monika D. Jürgens; Nuria Bachiller‐Jareno; Isabelle Fournier; Daniel S. Read (Limnology and Oceanography, 2024)
Excessive phytoplankton concentrations in rivers can result in the loss of plant and invertebrate communities, and threaten drinking water supplies. Whilst the physicochemical controls on algal blooms have been identified previously, how these factors combine to control the initiation, size, and cessation of blooms in rivers is not well understood. We applied flow cytometry to quantify diatom, chlorophyte, and cyanobacterial group abundances in the River Thames (UK) at weekly intervals from 2011 to 2022, alongside physicochemical data. A niche modeling approach was used to identify thresholds in water temperature, flow, solar radiation, and soluble reactive phosphorus (SRP) concentrations required to produce periods of phytoplankton growth, with blooms only occurring when all thresholds were met. The thresholds derived from the 2011 to 2018 dataset were applied to a test data set (2019–2022), which predicted the timing and duration of blooms at accuracies of > 80%. Diatoms and nano‐chlorophyte blooms were initiated by flow and water temperature, and usually terminated due to temperature and flow going out of the threshold range, or SRP and Si becoming limiting. Cyanobacterial bloom dynamics were primarily controlled by water temperature and solar radiation. This simple methodology provides a key understanding of phytoplankton community succession and inter‐annual variation and can be applied to any river with similar water quality and phytoplankton data. It provides early warnings of algal and cyanobacterial bloom timings, which support future catchment management decisions to safeguard water resources, and provides a basis for modeling changing phytoplankton bloom risk due to future climate change.

Reaction path model of the formation of abiotic immiscible hydrocarbon fluids in subducted carbonated serpentinites, Lanzo Massif (Western Italian Alps) - Jingyi Huang; Dimitri A. Sverjensky; Isabelle Daniel; Alberto Vitale Brovarone (Lithos, 2024)

Yttrium speciation variability in bauxite residues of various origins, ages and storage conditions - Julien Couturier; Pierre Tamba Oularé; Blanche Collin; Claire Lallemand; Isabelle Kieffer; Julien Longerey; Perrine Chaurand; Jérôme Rose; Daniel Borschneck; Bernard Angeletti; Stéven Criquet; Renaud Podor; et al. (Journal of Hazardous Materials, 2024)

Thermotopes-COH—A software for carbon isotope modeling and speciation of COH fluids - Antoine Boutier; Isabelle Martinez; Isabelle Daniel; Simone Tumiati; Guillaume Siron; Alberto Vitale Brovarone (Computers & Geosciences, 2024)

Complexity of graphite formation in response to metamorphic methane generation and transformation in an orogenic ultramafic body - Antoine Boutier; Isabelle Martinez; Olivier Sissmann; Samuele Agostini; Isabelle Daniel; Mark Van Baalen; Sara Mana; Alberto Vitale Brovarone (Geochimica et Cosmochimica Acta, 2024)

Natural seeding as an alternative to planting in black spruce-lichen woodlands - François Hébert; Isabelle Delisle; Marc Tremblay; Pascal Tremblay; Jean-François Boucher; Yan Boucher; Daniel Lord (Forest Ecology and Management, 2024)

Water-soluble polymers: Emerging contaminants detected, separated and quantified by a novel GPC/MALDI-TOF method - Eve C. Tarring; Isabelle Durance; Michael J. Harbottle; Robert Lucas; Daniel S. Read; Benjamin D. Ward (Environmental Pollution, 2024)

Within‐ and transgenerational stress legacy effects of ocean acidification on red abalone ( Haliotis rufescens ) growth and survival - Isabelle P. Neylan; Daniel S. Swezey; Sara E. Boles; Jackson A. Gross; Andrew Sih; John J. Stachowicz (Global Change Biology, 2024)
Understanding the mechanisms by which individual organisms respond and populations adapt to global climate change is a critical challenge. The role of plasticity and acclimation, within and across generations, may be essential given the pace of change. We investigated plasticity across generations and life stages in response to ocean acidification (OA), which poses a growing threat to both wild populations and the sustainable aquaculture of shellfish. Most studies of OA on shellfish focus on acute effects, and less is known regarding the longer term carryover effects that may manifest within or across generations. We assessed these longer term effects in red abalone ( Haliotis rufescens ) using a multi‐generational split‐brood experiment. We spawned adults raised in ambient conditions to create offspring that we then exposed to high pCO 2 (1180 μatm; simulating OA) or low pCO 2 (450 μatm; control or ambient conditions) during the first 3 months of life. We then allowed these animals to reach maturity in ambient common garden conditions for 4 years before returning the adults into high or low pCO 2 treatments for 11 months and measuring growth and reproductive potential. Early‐life exposure to OA in the F1 generation decreased adult growth rate even after 5 years especially when abalone were re‐exposed to OA as adults. Adult but not early‐life exposure to OA negatively impacted fecundity. We then exposed the F2 offspring to high or low pCO 2 treatments for the first 3 months of life in a fully factorial, split‐brood design. We found negative transgenerational effects of parental OA exposure on survival and growth of F2 offspring, in addition to significant direct effects of OA on F2 survival. These results show that the negative impacts of OA can last within and across generations, but that buffering against OA conditions at critical life‐history windows can mitigate these effects.

The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Efficacy of activated carbon filtration and ozonation to remove persistent and mobile substances – A case study in two wastewater treatment plants - Isabelle J. Neuwald; Matthias Muschket; Alina H. Seelig; Daniel Sauter; Regina Gnirss; Thomas P. Knepper; Thorsten Reemtsma; Daniel Zahn (Science of The Total Environment, 2023)

Trace fossils from Furnas formation (Paraná Basin) reveal a marine depositional environment - Kevin William Richter; Elvio Pinto Bosetti; Isabelle de Siqueira Tavares; Daniel Sedorko (Journal of South American Earth Sciences, 2023)

Formation of hydrocarbons favored by high pressure at subduction zone conditions - Jingyi Huang; Isabelle Daniel; Dimitri A. Sverjensky; Hervé Cardon; Gilles Montagnac (Chemical Geology, 2023)

Environmental drivers of earthworm communities along an elevational gradient in the French Alps - Quentin Gabriac; Pierre Ganault; Isabelle Barois; Eduardo Aranda-Delgado; Elisa Cimetière; Jérôme Cortet; Montan Gautier; Mickaël Hedde; Daniel F. Marchán; José Carlos Pimentel Reyes; Alexia Stokes; Thibaud Decaëns (European Journal of Soil Biology, 2023)

Methyl methacrylate thermal decomposition: Modeling and laser spectroscopy of species time-histories behind reflected shock waves - Isabelle C. Sanders; Nicholas M. Kuenning; Nicolas Q. Minesi; Daniel I. Pineda; R. Mitchell Spearrin (Fuel, 2023)

The potential of Meudon spectroheliograph for investigating long term solar activity and variability - Jean-Marie Malherbe; Isabelle Bualé; Daniel Crussaire; Florence Cornu; Thierry Corbard (Advances in Space Research, 2023)

Common microgeographical selection patterns revealed in four European conifers - Ivan Scotti; Hadrien Lalagüe; Sylvie Oddou‐Muratorio; Caroline Scotti‐Saintagne; Rose Ruiz Daniels; Delphine Grivet; François Lefevre; Philippe Cubry; Bruno Fady; Santiago C. González‐Martínez; Anne Roig; Isabelle Lesur‐Kupin; et al. (Molecular Ecology, 2023)
Microgeographical adaptation occurs when the effects of directional selection persist despite gene flow. Traits and genetic loci under selection can then show adaptive divergence, against the backdrop of little differentiation at other traits or loci. How common such events are and how strong the selection is that underlies them remain open questions. Here, we discovered and analysed microgeographical patterns of genomic divergence in four European and Mediterranean conifers with widely differing life‐history traits and ecological requirements ( Abies alba MIll., Cedrus atlantica [Endl.] Manetti, Pinus halepensis Mill. and Pinus pinaster Aiton) by screening pairs from geographically close forest stands sampled along steep ecological gradients. We inferred patterns of genomic divergence by applying a combination of divergence outlier detection methods, demographic modelling, Approximate Bayesian Computation inferences and genomic annotation to genomic data. Surprisingly for such small geographical scales, we showed that selection is strong in all species but generally affects different loci in each. A clear signature of selection was systematically detected on a fraction of the genome, of the order of 0.1%–1% of the loci depending on the species. The novel modelling method we designed for estimating selection coefficients showed that the microgeographical selection coefficient scaled by population size ( Ns ) was 2–30. Our results convincingly suggest that selection maintains within‐population diversity at microgeographical scales in spatially heterogeneous environments. Such genetic diversity is likely to be a major reservoir of adaptive potential, helping populations to adapt under fluctuating environmental conditions.

Estimating Sensible and Latent Heat Fluxes over an Inland Water Body Using Optical and Microwave Scintillometers - Adrien Pierre; Pierre-Erik Isabelle; Daniel F. Nadeau; Antoine Thiboult; Alexei Perelet; Alain N. Rousseau; François Anctil; Jaril Deschamps (Boundary-Layer Meteorology, 2022)

A new set of microsatellite markers for Phoxinus lumaireul senso lato , Phoxinus marsilii and Phoxinus krkae for population and molecular taxonomic studies - Matej Vucić; Mišel Jelić; Göran Klobučar; Dušan Jelić; Han Ming Gan; Chris Austin; Daniel Guyonnet; Isabelle Giraud; Thomas Becking; Frederic Grandjean (Journal of Fish Biology, 2022)
Minnows of the genus Phoxinus are common and an often highly abundant fish species in Palearctic freshwater habitats. Phoxinus species have a complex evolutionary history, phylogenetic relationships are not well understood and there are a number of unresolved taxonomic problems. There are currently 23 different mitochondrial genetic lineages identified in the genus Phoxinus , 13 of which are recognized as valid species. The taxonomic status of these lineages requires resolution, including the degree to which they can interbreed. Suitable nuclear molecular markers for studies of population divergence and interbreeding between morphotypes and mitochondrial lineages are lacking for Phoxinus species. Therefore, the authors developed a set of microsatellite markers using genomic information from Phoxinus lumaireul and tested their suitability for this and two related species, Phoxinus krkae and Phoxinus marsilii. Out of 16 microsatellite candidate loci isolated, 12 were found to be in Hardy–Weinberg equilibrium when tested on two P. lumaireul senso lato populations. Seven loci amplified across the three species, enabling the study of intraspecific genetic diversity and population structure within P. marsilii and P. krkae . The markers were able to clearly resolve differences among the three tested species, including the recently described P. krkae , and are therefore suitable for the detection of introgression and hybridization among populations consisting of mixtures of two or more of P. lumaireul s. l. , P. marsilii and P. krkae .

A critical comparison of integral projection and matrix projection models for demographic analysis: Reply - Daniel F. Doak; Ellen Waddle; Ryan E. Langendorf; Allison M. Louthan; Nathalie Isabelle Chardon; Reilly Dibner; Robert K. Shriver; Cristina Linares; Maria Begoña Garcia; Sarah W. Fitzpatrick; William F. Morris; Megan L. DeMarche (Ecology, 2022)

Clear-cutting without additional regeneration treatments can trigger successional setbacks prolonging the expected time to compositional recovery in boreal forests - Martin Barrette; Yan Boucher; Daniel Dumais; Isabelle Auger (European Journal of Forest Research, 2022)

Sex differences in neurobehavioral consequences of methamphetamine exposure in adult mice - Delaney L. Davis; Daniel B. Metzger; Philip H. Vann; Jessica M. Wong; Kumudu H. Subasinghe; Isabelle K. Garlotte; Nicole R. Phillips; Ritu A. Shetty; Michael J. Forster; Nathalie Sumien (Psychopharmacology, 2022)

Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Penelope K. Lindeque; Isabelle Hann; Helen E. Parry; Kathryn B. Cook; Anthony J. W. Lindley; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis , accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus- dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.

Towards a better understanding of the effect of anthropogenic habitat disturbance on the invasion success of non-native species: slugs in eastern Canadian forests - Anna Mazaleyrat; François Lorenzetti; Isabelle Aubin; Lisa A. Venier; Christian Hébert; Daniel Fortin; Angélique Dupuch (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Screening of grapevine red blotch virus in two European ampelographic collections - Jean-Sébastien Reynard; Justine Brodard; Nathalie Dubuis; Isabelle Kellenberger; Anne-Sophie Spilmont; David Roquis; Varvara Maliogka; Cécile Marchal; Sandrine Dedet; Ophélie Gning; Daniel Croll; Katia Gindro; et al. (Journal of Plant Pathology, 2022)
Grapevine red blotch virus (GRBV) is a recently identified virus that infects grapevine and has a severe impact on the grape industry in North America. Since the first description of the virus 8 years ago, clear progress has been made regarding our understanding of the GRBV pathosystem. However, questions remain regarding the origin of this pathogen and its spread outside North America, especially in Europe. In this study, we present the results of a large-scale GRBV survey in two European repositories; we targeted Vitis spp. accessions with diverse geographical origins. Of 816 accessions from different origins (50 different countries around the world), six accessions were infected by GRBV, all of which originated from the United States. We investigated the DNA virome of 155 grapevine accessions from the Swiss grapevine collection using high-throughput sequencing. We observed that virome of the Swiss grapevine collection was composed of several RNA viruses. In contrast, we did not detect any DNA viruses in the 155 Swiss grapevine accessions. This finding suggests that the abundance of DNA viruses infecting grapevines in Switzerland is either very low or non-existent. Our results and the findings of studies published since 2008 show that GRBV most likely originated in North America and subsequently spread to other viticultural areas in the world via unintentional movement of infected cuttings. According to our data, the most plausible scenario for the origin of GRBV is that the virus evolved from non- Vitis vinifera hosts and underwent a host jump to Vitis vinifera after its introduction to North America in the 1600s.

Safety assessment of cosmetics by read across applied to metabolomics data of in vitro skin and liver models - Carine Jacques; Emilien L. Jamin; Isabelle Jouanin; Cécile Canlet; Marie Tremblay-Franco; Jean-François Martin; Daniel Zalko; Yves Brunel; Sandrine Bessou-Touya; Laurent Debrauwer; Pierre-Jacques Ferret; Hélène Duplan (Archives of Toxicology, 2021)

Evaluating the congruence between DNA ‐based and morphological taxonomic approaches in water and sediment trap samples: Analyses of a 36‐month time series from a temperate monomictic lake - Joanna Gauthier; David Walsh; Daniel T. Selbie; Alyssa Bourgeois; Katherine Griffiths; Isabelle Domaizon; Irene Gregory‐Eaves (Limnology and Oceanography, 2021)
Paleolimnological studies are central for identifying long‐term changes, yet many studies rely on bioindicators that deposit detectable subfossils in sediments, such as diatoms and cladocerans. Emerging DNA‐based approaches are expanding the taxonomic diversity that can be investigated. However, as sedimentary DNA‐based approaches are expanding rapidly, calibration work is required to determine the advantages and limitations of these techniques. In this study, we assessed the congruence between morphological and DNA‐based approaches applied to sediment trap samples for diatoms and crustaceans using both intracellular and extracellular DNA. We also evaluated which taxa are deposited in sediment traps from the water column to identify potential paleolimnological bioindicators of environmental variations. Based on 18S rRNA gene amplicons, we developed and analyzed a micro‐eukaryotic, monthly time series that spanned 3 years and was comprised of paired water column and sediment trap samples from Cultus Lake, British Columbia, Canada. Comparisons of assemblages derived from our genetic and morphological analyses using RV coefficients revealed significant correlations for diatoms, but weaker correlations for crustaceans. Intracellular DNA reads correlated more strongly with diatom morphology, while extracellular DNA reads correlated more strongly with crustacean morphology. Additional analyses of amplicon sequence variants shared between water and sediment trap samples revealed a wide diversity of taxa to study in paleolimnology, including Ciliophora, Dinoflagellata, Chytridiomycota, Chrysophyceae, and Cryptophyceae. Partial RDAs identified significant environmental predictors of these shared assemblages. Overall, our study demonstrates the effectiveness of DNA‐based approaches to track community dynamics from sediment samples, an essential step for successful paleolimnological studies.

Silica-clay nanocomposites for the removal of antibiotics in the water usage cycle - Clément Levard; Karima Hamdi-Alaoui; Isabelle Baudin; Amélie Guillon; Daniel Borschneck; Andrea Campos; Mohamed Bizi; Florence Benoit; Corinne Chaneac; Jérôme Labille (Environmental Science and Pollution Research, 2021)

Seasonal patterns in greenhouse gas emissions from lakes and ponds in a High Arctic polygonal landscape - Vilmantas Prėskienis; Isabelle Laurion; Frédéric Bouchard; Peter M. J. Douglas; Michael F. Billett; Daniel Fortier; Xiaomei Xu (Limnology and Oceanography, 2021)
Lakes and ponds can be hotspots for CO 2 and CH 4 emissions, but Arctic studies remain scarce. Here we present diffusive and ebullition fluxes collected over several years from 30 ponds and 4 lakes formed on an organic‐rich polygonal tundra landscape. Water body morphology strongly affects the mixing regime—and thus the seasonal patterns in gas emissions—with ice‐out and autumnal turnover periods identified as hot moments in most cases. The studied thermokarst lake maintained relatively high ebullition rates of millennia‐old CH 4 (up to 3405 14 C YBP). Larger and deeper kettle lakes maintained low fluxes of both gases (century to millennium‐old), slowly turning into a CO 2 sink over the summer. During winter, lakes accumulated CO 2 , which was emitted during the ice‐out period. Coalescent polygonal ponds, influenced by photosynthesizing benthic mats, were continuous CO 2 sinks, yet important CH 4 emitters (modern carbon). The highest fluxes were recorded from ice‐wedge trough ponds (up to 96 mmol CO 2 equivalent m −2 d −1 ). However, despite clear signs of permafrost carbon inputs via active shore erosion, these sheltered ponds emitted modern to century‐old greenhouse gases. As the ice‐free period lengthens, scenarios of warmer and wetter conditions could favor both the production of CO 2 and CH 4 from thawing permafrost carbon, and CH 4 production from recently fixed carbon through an atmospheric CO 2 ‐to‐CH 4 shunt at sites in which primary production is stimulated. This must be carefully considered at the landscape scale, recognizing that older carbon stocks can be mineralized efficiently in specific locations, such as in thermokarst lakes.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Limitations to Use of Cassia grandis L. in the Revegetation of the Areas Impacted with Mining Tailings from Fundão Dam - Letícia Paiva de Matos; Heloísa Monteiro de Andrade; Claudio Sergio Marinato; Isabelle Gonçalves de Oliveira Prado; Daniel Gomes Coelho; Sebastián Giraldo Montoya; Maria Catarina Megumi Kasuya; Juraci Alves de Oliveira (Water, Air, & Soil Pollution, 2020)

Application and Evaluation of a Two-Wavelength Scintillometry System for Operation in a Complex Shallow Boreal-Forested Valley - Pierre-Erik Isabelle; Daniel F. Nadeau; Alexei O. Perelet; Eric R. Pardyjak; Alain N. Rousseau; François Anctil (Boundary-Layer Meteorology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Fine-grained reservoir sediments: an interesting alternative raw material for Portland cement clinker production - Baptiste Anger; Isabelle Moulin; Jean-Pierre Commene; François Thery; Daniel Levacher (European Journal of Environmental and Civil Engineering, 2019)

Bending the rules: exploitation of allochthonous resources by a top‐predator modifies size‐abundance scaling in stream food webs - Daniel M. Perkins; Isabelle Durance; Francois K. Edwards; Jonathan Grey; Alan G. Hildrew; Michelle Jackson; J. Iwan Jones; Rasmus B. Lauridsen; Katrin Layer‐Dobra; Murray S. A. Thompson; Guy Woodward (Ecology Letters, 2018)
Body mass–abundance ( M‐N ) allometries provide a key measure of community structure, and deviations from scaling predictions could reveal how cross‐ecosystem subsidies alter food webs. For 31 streams across the UK, we tested the hypothesis that linear log‐log M‐N scaling is shallower than that predicted by allometric scaling theory when top predators have access to allochthonous prey. These streams all contained a common and widespread top predator (brown trout) that regularly feeds on terrestrial prey and, as hypothesised, deviations from predicted scaling increased with its dominance of the fish assemblage. Our study identifies a key beneficiary of cross‐ecosystem subsidies at the top of stream food webs and elucidates how these inputs can reshape the size‐structure of these ‘open’ systems.

Deep TMS of the insula using the H-coil modulates dopamine release: a crossover [11C] PHNO-PET pilot trial in healthy humans - Saima Malik; Mark Jacobs; Sang-Soo Cho; Isabelle Boileau; Daniel Blumberger; Markus Heilig; Alan Wilson; Zafiris J. Daskalakis; Antonio P. Strafella; Abraham Zangen; Bernard Le Foll (Brain Imaging and Behavior, 2018)

Marine Mammals Exploring the Oceans Pole to Pole: A Review of the MEOP Consortium - Anne Treasure; Fabien Roquet; Isabelle Ansorge; Marthán Bester; Lars Boehme; Horst Bornemann; Jean-Benoît Charrassin; Damien Chevallier; Daniel Costa; Mike Fedak; Christophe Guinet; Mike Hammill; et al. (Oceanography, 2017)

Consensus Paper: Cerebellar Development - Ketty Leto; Marife Arancillo; Esther B. E. Becker; Annalisa Buffo; Chin Chiang; Baojin Ding; William B. Dobyns; Isabelle Dusart; Parthiv Haldipur; Mary E. Hatten; Mikio Hoshino; Alexandra L. Joyner; et al. (The Cerebellum, 2016)

Heterogeneous clinical spectrum of anti-SRP myositis and importance of the methods of detection of anti-SRP autoantibodies: a multicentric study - Cécile Picard; Thierry Vincent; Jean-Christophe Lega; Sophie Hue; Françoise Fortenfant; Daniela Lakomy; René-Louis Humbel; Joelle Goetz; Nicolas Molinari; Nathalie Bardin; Daniel Bertin; Catherine Johanet; et al. (Immunologic Research, 2016)

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Effect of pre-partum feed supplementation on post-partum ovarian activity, milk production and calf growth of small holder dairy Cattle in Cameroon - Pougue Henri Bayemi; Munji Victorine Nsongka; Isabelle Leinyuy; Edward Cottington Webb; Justin Mbanya Nchadji; Daniel Cavestany; Mike Bryant (Tropical Animal Health and Production, 2015)

Effect of cow parity and synchronization method with PGF2α on conception rates of Bos indicus cows in Cameroon - Pougue Henri Bayemi; Isabelle Leinyuy; Munji Victorine Nsongka; Edward Cottington Webb; Justin Mbanya Nchadji; Daniel Cavestany; BMA Oswin Perera (Tropical Animal Health and Production, 2015)

Former uranium mine-induced effects in caged roach: a multiparametric approach for the evaluation of in situ metal toxicity - Béatrice Gagnaire; Anne Bado-Nilles; Stéphane Betoulle; Rachid Amara; Virginie Camilleri; Isabelle Cavalié; Edith Chadili; Laurence Delahaut; Elodie Kerambrun; Daniel Orjollet; Olivier Palluel; Wilfried Sanchez (Ecotoxicology, 2015)

Trunk motor variability in patients with non-specific chronic low back pain - Jacques Abboud; François Nougarou; Isabelle Pagé; Vincent Cantin; Daniel Massicotte; Martin Descarreaux (European Journal of Applied Physiology, 2014)

Business oriented EU human cell and tissue product legislation will adversely impact Member States’ health care systems - Jean-Paul Pirnay; Alain Vanderkelen; Daniel De Vos; Jean-Pierre Draye; Thomas Rose; Carl Ceulemans; Nadine Ectors; Isabelle Huys; Serge Jennes; Gilbert Verbeken (Cell and Tissue Banking, 2013)

Gamma-hydroxybutyrate (GHB) and topiramate—clinically relevant drug interaction suggested by a case of coma and increased plasma GHB concentration - Tobias Weiss; Daniel Müller; Isabelle Marti; Caroline Happold; Stefan Russmann (European Journal of Clinical Pharmacology, 2013)

Characterization of endocrine disruptors from a complex matrix using estrogen receptor affinity columns and high performance liquid chromatography–high resolution mass spectrometry - Adeline Jondeau-Cabaton; Amélie Soucasse; Emilien L. Jamin; Nicolas Creusot; Marina Grimaldi; Isabelle Jouanin; Sélim Aït-Aïssa; Patrick Balaguer; Laurent Debrauwer; Daniel Zalko (Environmental Science and Pollution Research, 2013)

Ethnobotanical, morphological, phytochemical and molecular evidence for the incipient domestication of Epazote (Chenopodium ambrosioides L.: Chenopodiaceae) in a semi-arid region of Mexico - Isabelle Blanckaert; Martín Paredes-Flores; Francisco J. Espinosa-García; Daniel Piñero; Rafael Lira (Genetic Resources and Crop Evolution, 2012)

Buprenorphine versus methadone in pregnant opioid-dependent women: a prospective multicenter study - Isabelle Lacroix; Alain Berrebi; Daniel Garipuy; Laurent Schmitt; Yamina Hammou; Catherine Chaumerliac; Maryse Lapeyre-Mestre; Jean-Louis Montastruc; Christine Damase-Michel (European Journal of Clinical Pharmacology, 2011)

The Phage Therapy Paradigm: Prêt-à-Porter or Sur-mesure? - Jean-Paul Pirnay; Daniel De Vos; Gilbert Verbeken; Maia Merabishvili; Nina Chanishvili; Mario Vaneechoutte; Martin Zizi; Geert Laire; Rob Lavigne; Isabelle Huys; Guy Van den Mooter; Angus Buckling; et al. (Pharmaceutical Research, 2011)

Prenatal alcohol exposure and cortisol activity in 19-month-old toddlers: an investigation of the moderating effects of sex and testosterone - Isabelle Ouellet-Morin; Ginette Dionne; Sonia J. Lupien; Gina Muckle; Sylvana Côté; Daniel Pérusse; Richard E. Tremblay; Michel Boivin (Psychopharmacology, 2011)

Land‐use intensification reduces functional redundancy and response diversity in plant communities - Etienne Laliberté; Jessie A. Wells; Fabrice DeClerck; Daniel J. Metcalfe; Carla P. Catterall; Cibele Queiroz; Isabelle Aubin; Stephen P. Bonser; Yi Ding; Jennifer M. Fraterrigo; Sean McNamara; John W. Morgan; et al. (Ecology Letters, 2010)
Ecosystem resilience depends on functional redundancy (the number of species contributing similarly to an ecosystem function) and response diversity (how functionally similar species respond differently to disturbance). Here, we explore how land‐use change impacts these attributes in plant communities, using data from 18 land‐use intensity gradients that represent five biomes and > 2800 species. We identify functional groups using multivariate analysis of plant traits which influence ecosystem processes. Functional redundancy is calculated as the species richness within each group, and response diversity as the multivariate within‐group dispersion in response trait space, using traits that influence responses to disturbances. Meta‐analysis across all datasets showed that land‐use intensification significantly reduced both functional redundancy and response diversity, although specific relationships varied considerably among the different land‐use gradients. These results indicate that intensified management of ecosystems for resource extraction can increase their vulnerability to future disturbances. Ecology Letters (2010) 13: 76–86

Integrating life cycle costs and environmental impacts of composite rail car-bodies for a Korean train - Pascale Schwab Castella; Isabelle Blanc; Marcel Gomez Ferrer; Bastien Ecabert; Martyn Wakeman; Jan-Anders Manson; Daniel Emery; Seong-Ho Han; Jinglan Hong; Olivier Jolliet (The International Journal of Life Cycle Assessment, 2009)

Inhibition of intracellular dipeptide hydrolysis uncovers large outward transport currents of the peptide transporter PEPT1 in Xenopus oocytes - Gabor Kottra; Isabelle Frey; Hannelore Daniel (Pflügers Archiv - European Journal of Physiology, 2009)

Evidence for linkage of a new region (11p14) to eczema and allergic diseases - Michel Guilloud-Bataille; Emmanuelle Bouzigon; Isabella Annesi-Maesano; Jean Bousquet; Denis Charpin; Frédéric Gormand; Joëlle Hochez; Jocelyne Just; Arnaud Lemainque; Nicole Le Moual; Régis Matran; Françoise Neukirch; et al. (Human Genetics, 2008)

Phenotype analysis of mice deficient in the peptide transporter PEPT2 in response to alterations in dietary protein intake - Isabelle M. Frey; Isabel Rubio-Aliaga; Martina Klempt; Eckhard Wolf; Hannelore Daniel (Pflügers Archiv - European Journal of Physiology, 2006)

Multiple origin of metallicolous populations of the pseudometallophyte Arabidopsis halleri (Brassicaceae) in central Europe: the cpDNA testimony - MAXIME PAUWELS; PIERRE SAUMITOU‐LAPRADE; ANNE CATHERINE HOLL; DANIEL PETIT; ISABELLE BONNIN (Molecular Ecology, 2005)
The population structure of the pseudo‐metallophyte herb, Arabidopsis halleri , was studied using Polymerase Chain Reaction‐Restriction Fragment Length Polymorphism (PCR–RFLP) on chloroplast DNA (cpDNA). The history of metallicolous (M) populations showing increased zinc tolerance was investigated. Eight primer‐enzyme combinations out of 72 tested were applied to a total of 625 individuals from 28 widespread populations, 14 of them being M. Eleven distinct chlorotypes were found: five were common to nonmetallicolous (NM) and M populations, whereas six were only observed in one edaphic type (five in NM and one in M). No difference in chlorotype diversity between edaphic types was detected. Computed on the basis of chlorotype frequencies, the level of population differentiation was high but remained the same when taking into account levels of molecular divergence between chlorotypes. Isolation by distance was largely responsible for population differentiation. Geographically isolated groups of M populations were more genetically related to their closest NM populations than to each other. Our results suggest that M populations have been founded separately from distinct NM populations without suffering founding events and that the evolution towards increased tolerance observed in the distinct M population groups occurred independently.

Selection of Grifola frondosa and Fomitopsis pinicola strains resistant to Trichoderma viride in teflon tubes confrontation method - Isabelle Schiff Giovannini; Daniel Job; Abdelaziz Hmamda (Mycological Progress, 2004)

Spatial genetic structure within a metallicolous population of Arabidopsis halleri, a clonal, self‐incompatible and heavy‐metal‐tolerant species - FABIENNE VAN ROSSUM; ISABELLE BONNIN; STÉPHANE FÉNART; MAXIME PAUWELS; DANIEL PETIT; PIERRE SAUMITOU‐LAPRADE (Molecular Ecology, 2004)
Arabidopsis halleri , a close wild relative of A. thaliana , is a clonal, insect‐pollinated herb tolerant to heavy metals (Zn, Pd, Cd) and a hyperaccumulator of Zn and Cd. It is of particular interest in the study of evolutionary processes and phytoremediation. However, little is known about its population gene flow patterns and the structure of its genetic diversity. We used five microsatellite loci to investigate the genetic structure at a fine spatial scale (10 cm to 500 m) in a metallicolous population of A. halleri . We also studied the contributions made by clonal propagation and sexual reproduction (seed and pollen dispersal) to the genetic patterns. Clonal diversity was high ( D G > 0.9). Clonal spread occurs only at short distances (

Heavy Metal Determination in Atmospheric Deposition and Other Fluxes in Northern France Agrosystems - Sam Azimi; Philippe Cambier; Isabelle Lecuyer; Daniel Thevenot (Water, Air, & Soil Pollution, 2004)

Effects of the order of running and cycling of similar intensity and duration on pulmonary diffusing capacity in triathletes - Olivier Galy; Olivier Hue; Alain Boussana; Christelle Peyreigne; Isabelle Couret; Daniel Le Gallais; Jacques Mercier; Christian Préfaut (European Journal of Applied Physiology, 2003)

Microsatellite primer amplification by multiplexing: A first application toEucalyptus grandis - Gilles Chaix; Isabelle Chantal; Mireille Poitel; Sylvie Razafiarivelo; Daniel Verhaegen; Jean Charles Maillard (Plant Molecular Biology Reporter, 2002)

Assessment of genetic variation explained by markers for wool traits in sheep via a segment mapping approach - Ricardo Ponz; Carole Moreno; Daniel Allain; Jean M. Elsen; Fréderic Lantier; Isabelle Lantier; Jean C. Brunel; Miguel Pérez-Enciso (Mammalian Genome, 2001)

Structures of coenzyme F 420 in Mycobacterium species - Thomas Bair; Dale Isabelle; Lacy Daniels (Archives of Microbiology, 2001)

Regional characterization of a hamster–sheep somatic cell hybrid panel - Kamila Tabet-Aoul; Laurent Schibler; Daniel Vaiman; Anne Oustry-Vaiman; Isabelle Lantier; Nadhira Saidi-Mehtar; Edmond-Paul Cribiu; Frédéric Lantier (Mammalian Genome, 2000)

Biochemical and genetic studies of four patients with pyruvate dehydrogenase E1α deficiency - Cécile Marsac; Chantal Benelli; Isabelle Desguerre; Monique Diry; Françoise Fouque; L. De Meirleir; Gérard Ponsot; S. Seneca; Florence Poggi; Jean-Marie Saudubray; Marie-Thérèse Zabot; Daniel Fontan; et al. (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)